Expectations of Failure: Political Risks in the Moral Economy of Ignorance and Social Injustice - Adriana Mica; Mikołaj Pawlak; Paweł Kubicki (Sociologica, 2024)
We are observing how contemporary failure regimes increasingly challenge ignorance and social injustice, and how this opens expectations for public policy to move beyond effectiveness and to pursue more emancipatory and progressive aims. Policy reinterpretations and expectations of failure however, are not coming solely from critical and alternative groups in the society. They are first and foremost political, which raises the question how does the moral economy and epistemology of just futures unfold? What are the effects of political exploitation and contamination? Our answer is to review political risks of emancipatory activism in abortion debates, which manifest high levels of polarization and contestation in relation to reproductive justice and human rights. We map out various hazards, showing how they produce what we term post-failure, and sustain emancipation fantasies and alternative policy futures that are linked with oppression effects. With this exploration we see that addressing ignorance and social injustice in policymaking has never been more essential, yet also unpredictable and convoluted in the political risks that it poses.